2016
DOI: 10.17265/2159-5526/2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Community Responsibility as a Determinant of Corporate Responsibility

Abstract: Research on the social value of the bus industry in Australia revealed an inconsistency in findings between qualitative and quantitative results in relation to the nature of a bus operator's interaction with the community where they provide a transport service. As part of a larger research project that surveyed bus operators about their corporate social responsibility, bivariate analysis found that the responses to the embedded Sense of Community Index (SOCI) did not provide a predictor of the extent of a bus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Empirical scholarship on the community experience model in organizations has primarily focused on determining if SOC and SOC‐R are unique constructs in relation to each other, and to similar factors commonly studied in management science (e.g., Boyd & Nowell, 2014, 2017, 2020). Studies have also focused on the ability of community experiences to distinctively predict employee psychological and behavioral outcomes in accordance with the community experience model (Boyd & Nowell, 2017, 2020; Boyd et al, 2018; Cicognani et al, 2020; Lowe et al, 2016; Nowell & Boyd, 2014; Nowell et al, 2016; Pedersen et al, 2020; Yang, Wang, Hall, et al, 2020; Yang, Wang, Wang, et al, 2020), and how they operate in relation to other motivational constructs (Boyd & Nowell, 2020; Boyd et al, 2018; Brincker & Pedersen, 2020; Pedersen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical scholarship on the community experience model in organizations has primarily focused on determining if SOC and SOC‐R are unique constructs in relation to each other, and to similar factors commonly studied in management science (e.g., Boyd & Nowell, 2014, 2017, 2020). Studies have also focused on the ability of community experiences to distinctively predict employee psychological and behavioral outcomes in accordance with the community experience model (Boyd & Nowell, 2017, 2020; Boyd et al, 2018; Cicognani et al, 2020; Lowe et al, 2016; Nowell & Boyd, 2014; Nowell et al, 2016; Pedersen et al, 2020; Yang, Wang, Hall, et al, 2020; Yang, Wang, Wang, et al, 2020), and how they operate in relation to other motivational constructs (Boyd & Nowell, 2020; Boyd et al, 2018; Brincker & Pedersen, 2020; Pedersen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study indicated that the sense of responsibility had cross-context consistency: An individual's sense of responsibility in one context (e.g., family) had a strong predictive effect on his sense of responsibility in another context [34]. People not only have a need to be a part of community but also feel a sense of duty and responsibility toward their community [35,36]. Therefore, perhaps we can speculate on the relationship between SOC-R and altruistic behavior from studies of family responsibility and social responsibility.…”
Section: Introductionmentioning
confidence: 99%